Le travail d’articulation des encadrants de proximité : quels enjeux de production et de santé en horticulture ? - Corinne Gotteland Agostini; Valérie Zara-Meylan; Valérie Pueyo (Perspectives Interdisciplinaires sur le Travail et la Santé)
The functions of supervisors are dependent on changes in organizations. Today, their tasks are expanding, with new requirements and work controls modes based on management tools. Away from providing support, these developments seem rather complicate the work of supervisors, particularly in horticulture, a sector where production processes require a dynamic management that cannot be entirely planned upstream due to the natural element, the living products and incidents encountered. The analysis of eight supervisors’ activity shows different positions and relational networks, with large common characteristics which specify conditions of their work. Their activity is being built in various work situations. We highlight the articulations they ensure to manage conflicting requirements, and we analyze the ways in which they integrate them into the organization and the prescription they design. For that, they hold multiple issues of quality and health, and ensure both the sustainability of the production and the work.